MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA KARTU ANGKA KELAS III SEKOLAH DASAR - Betty Era Natalia; Yantoro Yantoro; Andi Gusmaulia Eka Putri (Jurnal Tunas Pendidikan, 2024)
Describe the increase in students' mathematical understanding abilities through the application of number card learning media in mathematics content in elementary schools. This research is classroom action research, which was carried out in two cycles, where each cycle was carried out in two meetings and consisted of four stages, namely planning, implementation, observation and reflection. The subjects of this research were class III students at SDN 134/i Merbau with 14 students consisting of 8 men and 6 women. Data collection techniques in this research are observation and tests. The observation instruments for this research are contextual teaching and learning indicator observation sheets and teacher activity observation sheets. The instrument for measuring students' arithmetic operation skills is to carry out tests in each cycle. The data analysis techniques used are qualitative and quantitative. The results of the research show that there is an increase in mathematical understanding abilities in class III elementary school students, which can be seen from the results of student observations in cycle 1, meeting 1 with a percentage of 69.86%, in cycle 1, meeting 2, there was an increase of 77.97%. Cycle 2 meeting 1 with a percentage of 78.96% and in cycle 2 meeting 2 it increased to 82.73%. Next, the test results, namely the pre test, with a classical percentage of 23.07%. The post test results in cycle 1 achieved classical completeness of 57.14%. Then the post test results in cycle 2 reached classical completeness of 78.57%.